Software solution for clinical protocol management - Almeida, João Rafael Duarte de (2019)
Decision support systems are currently important tools to guide the clinician’s decisions and to help on the patient’s treatments. These systems have been studied over the last decades, leading to some well-defined best practices for building new solutions. This project had the objective of building a clinical decision system with a core engine based on predefined rules, which can be customized by end-users. This work had as main motivation the treatment of diabetic inpatients and outpatients, in hospital services others than endocrinology. To keep the solution generic, the system does not depend on any specific patient data, neither on the protocols. This application follows the client-server model. based on a microservice architecture, providing a modern web user interface. The project was carried out in a close collaboration with the Hospital Center of Baixo do Vouga, resulting in a solution that can assists health professionals in the treatment of patients, reducing errors and providing a better monitoring of health care services.